Optical Characterization of Fresh and Photochemically Aged Aerosols Emitted from Laboratory Siberian Peat Burning - Iaukea-Lum, Michealene; Bhattarai, Chiranjivi; Sengupta, Deep; Samburova, Vera; Khlystov, Andrey Y.; Watts, Adam C.; Arnott, William P.; Moosmüller, Hans (Atmosphere, 2022)
Carbonaceous aerosols emitted from biomass burning influence radiative forcing and climate change. Of particular interest are emissions from high-latitude peat burning because amplified climate change makes the large carbon mass stored in these peatlands more susceptible to wildfires and their emission can affect cryosphere albedo and air quality after undergoing transport. We combusted Siberian peat in a laboratory biomass-burning facility and characterized the optical properties of freshly emitted combustion aerosols and those photochemically aged in an oxidation flow reactor (OFR) with a three-wavelength photoacoustic instrument. Total particle count increased with aging by a factor of 6 to 11 while the total particle volume either changed little (<8%) for 19 and 44 days of equivalent aging and increased by 88% for 61 days of equivalent aging. The aerosol single-scattering albedo (SSA) of both fresh and aged aerosol increased with the increasing wavelength. The largest changes in SSA due to OFR aging were observed at the shortest of the three wavelengths (i.e., at 405 nm) where SSA increased by less than ~2.4% for 19 and 44 days of aging. These changes were due to a decrease in the absorption coefficients by ~45%, with the effect on SSA somewhat reduced by a concurrent decrease in the scattering coefficients by 20 to 25%. For 61 days of aging, we observed very little change in SSA, namely an increase of 0.31% that was caused a ~56% increase in the absorption coefficients that was more than balanced by a somewhat larger (~71%) increase in the scattering coefficients. These large increases in the absorption and scattering coefficients for aging at 7 V are at least qualitatively consistent with the large increase in the particle volume (~88%). Overall, aging shifted the absorption toward longer wavelengths and decreased the absorption Ångström exponents, which ranged from ~5 to 9. Complex refractive index retrieval yielded real and imaginary parts that increased and decreased, respectively, with the increasing wavelength. The 405 nm real parts first increased and then decreased and imaginary parts decreased during aging, with little change at other wavelengths.